KONDISI SANITASI DASAR DENGAN KEJADIAN DIARE PADA MASYARAKAT - Manik, Erba Kalto; Tanjung, Risnawaty; Ambarita, Monika putri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Diarrhea is a health problem that is still often experienced by the community and is a cause of high morbidity and mortality rates. The environmental factors that play a role are basic sanitation conditions which include clean water supply facilities, family latrine facilities, garbage disposal facilities and waste water disposal facilities. The research method used in this study is quantitative analysis using a Cross Sectional Design which aims to determine the condition of basic sanitation facilities. with the incidence of diarrhea in the community. The number of samples used in this study amounted to 65 samples. Data analysis was performed using the chi square test. The results showed that there was a significant relationship between clean water supply facilities and the incidence of diarrhea in the community with p value = 0.000 (p < 0.05), and sewerage facilities (SPAL) with p value = 0.000 (p < 0.05). while not significant are latrine facilities p value (0.702) and waste disposal facilities with the incidence of diarrhea in the community p value = 0.448 (p > 0.05).